Pengaruh Pelatihan Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan di PT Indo Husada Utama - Putra, Boby Bala; Sumbogo, Ignatius Ario (STREAMING, 2023)
The purpose of this study was to determine whether there is an effect of job training, work environment on employee performance at PT Indo Husada Utama. This study used a quantitative method by conducting surveys and tests on 30 employees at PT Indo Husada Utama. The sampling method is saturated sampling which is part of the non-probability sampling technique. Data collection was carried out by distributing questionnaires using a Likert scale to measure each statement. The tests carried out were validity test, reliability test, classic assumption test, hypothesis test, and multiple regression test with the help of the IBM SPSS Statistics 25 program. The results showed that job training variables has a significant effect on employee performance, work environment variables have no significant effect on employee performance, and job training and work environment variables have a significant effect on employee performance